Outcomes of Fixed-Hinged Knee Prosthesis for Distal Femoral Osteosarcoma in Skeletally Immature Patients: First Results - Zhao, Zhiqing; Yang, Yi; Yan, Taiqiang; Tang, Xiaodong; Yang, Rongli; Guo, Wei (The Journal of Knee Surgery, 2021)
The best surgical choice for distal femur osteosarcoma in skeletally immature patients remains controversial. A fixed hinged knee prosthesis has been designed to preserve the growth plates in the adjacent tibia, expecting tibial growth to be continued. This study aims to report the (1) clinical outcomes after prosthetic replacement, (2) postoperative complications, and (3) length of discrepancy of the operative tibia with the unaffected tibia. Thirty-four skeletally immature patients (averaged 9 years at surgery; range, 5–12 years) with distal femoral osteosarcoma underwent placement of this hinged knee prosthesis between January 2015 and August 2018. Postoperative function and complications were assessed. Length discrepancy was measured using a series of full-length standing anteroposterior radiographs of the bilateral lower extremity. The average follow-up duration was 34 months (2.8 years). In the last follow-up, four patients expired because of pulmonary metastasis. Two patients presented with local recurrence of the soft tissue. Postoperatively, the flexion range of the knee joint range was between 100 and 130 degrees, with an average of 115.2 degrees. The mean functional score of living patients evaluated using the Musculoskeletal Tumor Society scoring system was 89.2% (range, 76.7–100%). Types 1 (three patients), 2 (one patient), 3 (two patients), and 5 (two patients) complications exist. Among them, three patients received revision surgery. The proximal tibial physis still grew after surgery, with an average of 74.3% (range, 30–100%) growth potential compared with the unaffected proximal tibial physis. Moreover, 27 children exhibited tibial length discrepancy compared with the contralateral tibia, and the mean discrepancy in tibial length was 1.1 cm (range, 0.2–3.1 cm). This hinged knee prosthesis can keep the growth potential in the adjacent tibia, provides satisfying functional outcomes, and has a lower postoperative complication rate. Thus, it could serve as an alternative intervention for distal femoral osteosarcoma in skeletally immature patients.
Keywords: osteosarcoma; tumor prosthesis; limb salvage; children